Implementation of PMDL and DRM in OpenSees for Soil-Structure Interaction Analysis - Uzun, Sefa; Ayvaz, Yusuf (MDPI, 2024)
It is widely acknowledged that the effects of soil-structure interaction (SSI) can have substantial implications during periods of intense seismic activity; therefore, accurate quantification of these effects is of paramount importance in the design of earthquake-resistant structures. The analysis of SSI is typically conducted using either direct or substructure methods. Both of these approaches involve the use of numerical models with truncated or reduced-order computational domains. To ensure effective truncation, it is crucial to employ boundary representations that are capable of perfectly absorbing outgoing waves and allowing for the consistent application of input motions. At present, such capabilities are not widely available to researchers and practicing engineers. In order to address this issue, this study implemented the Domain Reduction Method (DRM) and Perfectly Matched Discrete Layers (PMDLs) in OpenSees. The accuracy and stability of these implementations were verified through the use of vertical and inclined incident SV waves in a two-dimensional problem. In terms of computational efficiency, PMDLs require a shorter analysis time (e.g., with PMDLs, the analysis concluded in 35 min as compared to 250 min with extended domain method) and less computational power (one processor for PMDLs against 20 processors for the extended domain method) thus offering a balance between accuracy and efficiency. Furthermore, illustrative examples of the aforementioned implemented features are presented, namely the response analysis of single-cell and double-cell tunnels exposed to plane waves inclined at an angle.
Keywords: Perfectly Matched Discrete Layer; Domain Reduction Method; soil-structure interaction; OpenSees; finite element method; ABSORBING BOUNDARY-CONDITIONS; EARTHQUAKE RESPONSE ANALYSIS; PERFECTLY MATCHED LAYERS; LOCALIZED REGIONS; SEISMIC RESPONSE; DISCRETE LAYERS; ELASTODYNAMICS; PROPAGATION; ELEMENTS; Chemistry; Engineering; Materials Science; Physics